«Pocket libraries» of Transbaikal Buddhists and culture of small-format publications: medical and astrological treatises - A. A. Bazarov; D. L. Dorzhieva; S. M. Naidanova (Библиосфера)
«Pocket libraries» of Transbaikal Buddhists is a source of reliable information on the Buddhist book culture development in the region. Consequently, these texts are of interest to any modern specialist in the field. These collections have included texts of different genres. Genres of «medicine» and «astrology» are the most popular. The level of the Transbaikal Buddhists literary culture is demonstrated by specific texts.